Law of banking and negotiable instruments - Igweike, Kingsley (Onitsha, Nigeria : Africana-FEP Publishers, 1991)
Provides an indepth analysis of the banking law and negotiable instrument with emphasis on the Nigerian situation.
Includes bibliographical references.
oif 03/03/15
Loan
Keywords: Banking law -- Nigeria; Negotiable instruments -- Nigeria